Knowledge, Attitude and Practices of Standard Precaution among Nurses in Middle-East Hospital - Noorasyikin Mohd-Nor,; Yee , Bit-Lian (2019)
Introduction: Staff nurses are exposed to many blood and other fluids in the course of their day to day activities in Intensive Care Unit. Purpose of this survey is to assess the level of knowledge, attitudes and practices of standard precaution among nurses in Intensive Care unit, in Middle East Hospital. Method: This was a cross-sectional study and undertaken among nurses by self-administered and anonymous questionnaire that randomly selected in Intensive Care Unit, Middle East Hospital. Results: Female nurses accounted for majority of the respondents which covered 66.7% (n = 44) while male nurses make up around 33.3% (n = 22) of the nursing workforce in the study. 53% (n = 35) of the respondents reported not having any basic exposure or training in infection control practices, while the other 47% (n = 31) respondents received their training or basic exposure in infection control practices. Majority of the participants had high level of knowledge. Conclusion: In accordance to the self-reported questionnaires, 77% (n = 51) of the respondents practice good practices of standard precaution. The knowledge, attitude and compliance among ICU nurses in the middle-east hospital towards standard precaution was adequate.